2002
DOI: 10.1074/jbc.m205826200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A Enhances Leukocyte Binding by Human Intestinal Microvascular Endothelial Cells through Inhibition of p38 MAPK and iNOS

Abstract: The calcineurin inhibitor cyclosporine A (CsA) modulates leukocyte cytokine production but may also effect nonimmune cells, including microvascular endothelial cells, which regulate the inflammatory process through leukocyte recruitment. We hypothesized that CsA would promote a proinflammatory phenotype in human intestinal microvascular endothelial cells (HIMEC), by inhibiting inducible nitric-oxide synthase (iNOS, NOS2)-derived NO, normally an important mechanism in limiting endothelial activation and leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
6
62
0
Order By: Relevance
“…Transcriptional factors [i.e., nuclear factor kappa B (NF-κB)] are involved in the expression of endothelial adhesion molecules [4]. In this regard, CYA attenuates adhesion interaction and transendothelial migration and infiltration of neutrophils by decreasing endothelial expression of cell adhesion molecules (E-selectin, intercellular adhesion molecule 1, and vascular cell adhesion molecule 1) and inhibiting the antiapoptotic NF-κB, a central transcription factor mediating inflammatory injury [16]. CYA causes consistent inhibition of chemotactic migration, superoxide generation, and chemokine (IL-8) production by neutrophils in a dose-dependent manner.…”
Section: Cyclosporine A: Mechanisms Of Actionmentioning
confidence: 99%
“…Transcriptional factors [i.e., nuclear factor kappa B (NF-κB)] are involved in the expression of endothelial adhesion molecules [4]. In this regard, CYA attenuates adhesion interaction and transendothelial migration and infiltration of neutrophils by decreasing endothelial expression of cell adhesion molecules (E-selectin, intercellular adhesion molecule 1, and vascular cell adhesion molecule 1) and inhibiting the antiapoptotic NF-κB, a central transcription factor mediating inflammatory injury [16]. CYA causes consistent inhibition of chemotactic migration, superoxide generation, and chemokine (IL-8) production by neutrophils in a dose-dependent manner.…”
Section: Cyclosporine A: Mechanisms Of Actionmentioning
confidence: 99%
“…Therefore, the p38 MAPK signal transduction pathway plays an important role in the inflammatory response. Rafiee et al (2002) found that p-p38MAPK was higher in IBD patients than in normal people, and positively correlated with the degree of intestinal inflammation (Zhao et al, 2011). Waetzig et al (2002) found that during IBD intestinal epithelial injury, the activity of p38MAPK was significantly increased, and revealed that by tissue immunohistochemistry high p38MAPK expression in macrophages and neutrophils of the intestinal lamina propria.…”
Section: Discussionmentioning
confidence: 99%
“…It could be activated by various cytokines (TNF-a, IL-1), lipopolysaccharide, stress stimuli (heat shock, hyperosmolar injury, ischemia -reperfusion) (Rafiee et al, 2002;Jameel et al, 2009). A number of studies have shown that cells exposed to the above stimuli could activate p38MAPK, which would then regulate the inflammatory response by the following means.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies demonstrating the inhibitory effect of immunosuppressor drugs upon leukocyte migration. In vitro studies have shown that cyclosporin A (CLPA) inhibited intercellular adhesion molecule-1 (ICAM-1), vascular adhesion molecule-1, (VCAM-1), E-selectin, P-selectin, platelet/endothelial cell adhesion molecule-1 (PECAM-1) and the L-selectin ligand CD34 in human endothelial cells (Markovic et al, 2002;Rafiee et al, 2002;Zhou et al, 2004). CLPA reduced also endothelial and keratinocyte ICAM-1 expression in patients with psoriasis (Servitje et al, 1996).…”
Section: Discussionmentioning
confidence: 99%